Techno-Economic Environmental Risk Analysis (TERA) in hydrogen farms - Alssalehin, Esmaeil; Holborn, Paul; Pilidis, Pericles (MDPI, 2025)
This study presents a techno-economic environmental risk analysis (TERA) of large-scale green hydrogen production using Alkaline Water Electrolysis (AWE) and Proton Exchange Membrane (PEM) systems. The analysis integrates commercial data, market insights, and academic forecasts to capture variability in capital expenditure (CAPEX), efficiency, electricity cost, and capacity factor. Using Libya as a case study, 81 scenarios were modelled for each technology to assess financial and operational trade-offs. For AWE, CAPEX is projected between $311 billion and $905.6 billion for 519 GW (gigawatts) of installed capacity, equivalent to 600–1745 $/kW. PEM systems show a wider range of $612 billion to $1020 billion for 510 GW, translating to 1200–2000 $/kW. Results indicate that AWE, while requiring greater land use, provides significant cost advantages due to lower capital intensity and scalability. In contrast, PEM systems offer compact design and operational flexibility but at substantially higher costs. The five most economical scenarios for both technologies consistently feature low CAPEX and high efficiency, while sensitivity analyses confirm these two parameters as the dominant cost drivers. The findings emphasise that technology choice should reflect context-specific priorities such as land availability, budget, and performance needs. This study provides actionable guidance for policymakers and investors developing cost-effective hydrogen infrastructure in emerging green energy markets.
Keywords: 40 Engineering; 33 Built Environment and Design; 51 Physical Sciences; 7 Affordable and Clean Energy; capital expenditure (CAPEX); efficiency; levelized electricity cost (LEC); capacity factor; green hydrogen; sensitivity analysis; environmental sustainability